Gemcitabine alone versus gemcitabine plus cisplatin for the treatment of patients with locally advanced and/or metastatic pancreatic adenocarcinoma: A retrospective analysis of multicenter study - Inal, A.; Isikdogan, A.; Kos, T.; Algin, E.; Gumus, M.; Dikilitas, M.; Uncu, D. (Amer Soc Clinical Oncology, 2011)
[Abstract Not Available]